A Book of Bones A book of bones - Connolly, John, 1968- (New York : Emily Bestler Books, Atria, 2019)
He is our best hope. He is our last hope. On lonely moor in the northeast of England, the body of a young woman is discovered near the site of a vanished church. In the south, a girl lies buried beneath a Saxon mound. To the southeast, the ruins of a priory hide a human skull. Each is a sacrifice, a summons. And something in the darkness has heard the call. But another is coming: Parker the hunter, the avenger. From the forests of Maine to the deserts of the Mexican border, from the canals of Amsterdam to the streets of London, he will track those who would cast this world into darkness. Parker fears no evil. But evil fears him.
"A thriller"--Book jacket front cover.
Keywords: Parker, Charlie "Bird" -- (Fictitious character) -- Fiction; Private investigators -- Fiction; Human sacrifice -- Fiction; England -- Fiction; Thrillers (Fiction); Paranormal fiction; Detective and mystery fiction